PENGAKUAN PENGANGKATAN ANAK BERDASARKAN HUKUM ADAT DALAM PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 - Prasetyo, Agung Basuki (Fakultas Hukum, Universitas Diponegoro, 2019)
ABSTRACTThe majority of the public still considers the descendant (son) is a very essential element for a family that wishes to remain intact. So the importance of the descendants in the family, it can be potentially polygamous or occurrence of a divorce. Therefore, adoption is an alternative that can be done, in order that the purpose of marriage is to form a happy and eternal family come true. The implementation of the adoption on the basis of custom or customary law still do in order the life of indigenous peoples, since the custom is an expression of the belief that so long embedded, hereditary, thus leading adherence to customary law on any of their citizens. With regard to the recognition of adoption is done based on customary law in the Government Regulation Number 54 of the year 2007, there are clauses that are not singkron associated with recognition of the adoption is carried out on the basis of customary law . I.e. in article 1 point 1 asserted that the adopted child is recognized when it is done on the basis of a decision or determination of the Court. However, in article 8, there is a recognition of how adoption in customs. Next up in article 9 paragraph (1), still contains provisions related to the recognition of the institution of adoption is done based on custom.